Alija Izetbegović ‘s contributions to socio-political and religious thought - Delagic, Lejla; Ushama, Thameem (Hamdard Foundation Pakistan, 2022)
This paper explores the socio-political and religious thoughts of Alija Izetbegović, a Bosnian intellectual-turned-politician and one of the Islamic thinkers in ex-Yugoslavia in the 20th century. It applies descriptive and analytical methods to examine the contributions of Izetbegović in the socio-historical context, with particular reference to the Young Muslims movement. It studies the tribulations he endured due to persecution by the Communist Yugoslav authorities. Izetbegović's thought is a response to a twofold equally negative influence on Muslim intellectuals and leaders of the time – the traditionalists whose emphasis on rituals obstructed the reform and the modernists who blindly followed what Izetbegović considered un-Islamic sources. As a solution, Izetbegović advocated attaining personal freedom through education and establishing closer ties among Muslim countries from Indonesia to Morocco.